Study on Potentiation of ATRA Activity in HL-60 Cells by Targeting Methylation Enzymes - Liau, Ming C.; Kim, Jai-Hyun; Fruehauf, John P. (New Frontiers in Medicine and Medical Research Vol. 11, 2021)
All Trans Retinoic Acid (ATRA) is a Differentiation Inducer (DI) of Acute Promyelocytic Leukemia (APL) with proven clinical utility. Its benefits for other types of Acute Myelocytic Leukemia (AML) have been limited. In APL, ATRA targets the PML-RARA (promyelocytic leukemia/retinoic acid receptor-alpha)/DNA methyltransferase (DNMT)/Histone Deacetylase (HDAC) complex, facilitating its degradation, leading to loss of gene silencing and Terminal Differentiation (TD). In other forms of AML, ATRA targeting of WT RARA as a single agent fails to modulate the epigenetic changes blocking differentiation. However, when combined with agents that inhibit DNMT, such as 5-azacytidine, ATRA shows improved in vitro and clinical activity against AML. We previously demonstrated that targeting the methylation enzyme complex (MMS), consisting of Methionine Adenosyltransferase (MAT), Methyltransferase (MT) and S-Adenosylhomocysteine Hydrolase (SAHH), induced differentiation in the AML M2 HL-60 cell line model. Inhibitors of the ternary methylation enzyme complex act as Differentiation Helper Inducers (DHIs). While they are unable to induce significant terminal differentiation by themselves, they potentiate the action of DI’s. We report here that DHIs that destabilize SAHH potentiate the capacity of ATRA to induce terminal differentiation in both sensitive and resistant HL-60 cells in vitro. We also evaluated Tyrosine Kinase Inhibitors (TKIs) that interfere with the production of the stabilizing factor of SAHH, and steroid analogs that compete with the endogenous steroid stabilizing factor of SAHH. While 72% of early passage (sensitive) HL-60 cells demonstrated induction of Terminal Differentiation (TD) after exposure to 1\(μ\)M concentrations of ATRA, only 43% of late passage (resistant) cells showed TD. When ATRA was combined with TKI imatinib mesylate or with the steroid analogs resveratrol or \(β\)-sitosterol, agents with no innate capacity to induce differentiation, late passage HL-60 cell TD increased significantly to 98%, 99% and 94% of cells, respectively. Only modest improvements in TD percentages were seen for combinations of ATRA with cytotoxic chemotherapy agents: ATRA plus topotecan: 76%; ATRA plus oxaliplatin: 63%; ATRA plus paclitaxel: 59%. Combining ATRA with agents that interfere with maintenance of the methyl group pool potentiated its effects on an AML M2 cell line, and potentially in other forms of AML.